DAKWAH TANPA EKSTRIMISME DITINJAU DARI PERSPEKTIF SOSIOLOGI DAKWAH - Sumintak; Nuraini (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2023)
The increase in the da'wah movement in Indonesia is marked by many religious studies, but lately da'wah is often misunderstood in some circles. In the reality of everyday life, we often hear, read, and even see someone or a group feeling that they have done da'wah amaliyah. In fact, what is being done is still a lot of inequality, for example we see that there are still some cases of hate speech carried out by preachers which lead to the legal realm due to preaching that does not reflect Islamic values ​​because they feel they have power in the form of authority to spread threats and hatred through da'wah. delivered to the mad'u, as if the da'wah of Islam looks very scary. This kind of situation must be immediately presented with Islamic da'wah models that save and soothe The research was carried out using a phenomenological-critical approach by looking at how socio-religious phenomena are in the reality of everyday life. Sources of data that are discussed in this study using library research obtained from books, journal articles, websites, and through reading on social media. Basically, da'wah is an obligation inherent in every Muslim, a strategy is needed in da'wah by developing several models of da'wah that are very relevant to the realities of social life in the era of globalization. This is done to make each of us aware that we can spread da'wah messages with kindness so as not to damage the good image of Islamic da'wah which provides peace and safety for all people.